Empireland : how imperialism has shaped modern Britain - Sanghera, Sathnam (UK : Viking, an imprint of Penguin Books, 2021)
In his brilliantly illuminating book, Sathnam Sanghera demonstrates how so much of what we consider to be modern Britain is actually rooted in our imperial past. In prose that is, at once, both clear-eyed and full of acerbic wit, Sanghera shows how our past is everywhere: from how we live to how we think, from the foundation of the NHS to the nature of our racism, from our distrust of intellectuals in public life to the exceptionalism that imbued the campaign for Brexit and the government's early response to the Covid crisis. And yet empire is a subject, weirdly hidden from view.
Includes bibliography and index.
Keywords: Nationalkaraktär; Kollektivt minne; Nationell identitet; Sociala förhållanden; Nationalism; National characteristics; Collective memory; Storbritannien; kansallinen identiteetti; brittiläisyys; kollektiivinen muisti; imperialismi; kolonialismi; sosiaalinen kehitys; yhteiskuntajärjestelmät; poliittinen historia; historia; nationell identitet; brittiskhet; kollektivt minne; imperialism; kolonialism; social utveckling; samhällssystem; politisk historia; historia; Iso-Britannia; Storbritannien